2016
DOI: 10.1177/0021886316648774
|View full text |Cite
|
Sign up to set email alerts
|

The Critical Roles of Task Conflict and Job Autonomy in the Relationship Between Proactive Personalities and Innovative Employee Behavior

Abstract: We examine why and when proactive personality is beneficial for innovative behavior at work. Based on a survey among 166 employees working in 35 departments of a large municipality in the Netherlands we show that an increase in task conflicts explains the positive relation between a proactive personality and innovative employee behavior. This process is moderated by job autonomy in such a way that the relationship between proactive personality and task conflict is particularly strong under low compared with hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
74
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(89 citation statements)
references
References 84 publications
5
74
0
3
Order By: Relevance
“…The work pressure increasing while the job control decreasing may be lead nurses unable to take full advantage of the innovative resources provided by the organisation. Giebels, Reuver, Rispens, and Ufkes () found employees with higher autonomy can contribute to innovation through the creation of new ideas. When job control was as an incentive, nurses could increase opportunities to access information and resources, growth promotion, develop interpersonal relationships and build networks outside the office, which is vital for innovation behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…The work pressure increasing while the job control decreasing may be lead nurses unable to take full advantage of the innovative resources provided by the organisation. Giebels, Reuver, Rispens, and Ufkes () found employees with higher autonomy can contribute to innovation through the creation of new ideas. When job control was as an incentive, nurses could increase opportunities to access information and resources, growth promotion, develop interpersonal relationships and build networks outside the office, which is vital for innovation behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…Gong, Cheung, Wang, and Huang () examined how proactivity was related to creativity through seeking informational resources and exchanging these resources with others. The study by Giebels, de Reuver, Rispens, and Ufkes () further highlights that proactive personality leads to employee's innovative behaviour. We therefore argue for a positive relationship between proactive personality and IWB.…”
Section: Theoretical Model and Hypothesesmentioning
confidence: 97%
“…Therefore, there is a reason to believe that work discretion or job autonomy affects proactive behaviors resulting in organizational failure which raises task conflicts among coworkers (Giebels et al, 2016). Frese and Fay (2001) indicated that employees are seen as proactive when they focus on anticipatory actions which include adoption of changes in how the jobs, roles, and tasks are executed.…”
Section: Discussionmentioning
confidence: 99%